Sistem Informasi Loyalty Program di Layanan Penjualan Produk Software pada Bagian Point of Sales PT. XYZ - Erwin Suhandono; Agung Trilaksono Suwarto Putra (Fakultas Teknik Universitas Pancasila, 2021)
This research is backed by customer loyalty to the point of sales service tends to decline due to the difficult marketing part of managing customer data manually in accepting and responding to questions related to Web application features and help with how to use them, as more and more customers become difficult to control and track in each issue. The subject in this study is the customer service Manager. Data source is selected using special criteria with the condition of user who experienced directly the event that became the focus of research, able to retell the events that have been experienced, and willing to be a research user who get the conclusion that it needs a system to manage customer data, conduct promotional activities and see the growth of customers online. The data collection techniques in this study use observation methods and library studies. From the results of the research that has been implemented to implement the results of the research into the loyalty program information system in the software product sales service at the point of sales of PT. XYZ in the form of a website to manage customer data by the marketing and Android applications section for customers.